Impact Of Cataract Surgery on Quality of Life in People Aged 50 Years and Above in A Tertiary Care Hospital in Odisha, East India - Sharma, Dhananjaya; Pattnaik, Satyajit; Kuppusamy, Kumaresan; Bhoorsamy, Ashok; Panigrahi, Om Prakash (National Journal of Community Medicine, 2015)
Introduction: Cataract surgeries have brought about a significant improvement in visual acuity in the patients. This study tried to find the improvement in the general and visual quality of life after cataract surgery apart from the improvement in visual impairment. Method: In this prospective study, 231 patients above the age of 50 years who underwent cataract surgery between February 2008 and January 2009 were followed up after six month of surgery. Both vision related quality of life and generic health related quality of life was assessed using WHO/PBD VF 20 and EuroQol (EQ-5D) questionnaire respectively. Results: Out of 231 participants, 204 could be followed up at six months. The proportion of people with a visual acuity of > 6/60 increased from 10.8% to 85.8%. Overall vision related quality of life improved significantly (p<0.001). There was significant improvement in general quality of life over all five domains of mobility, self-care, usual activity, pain and anxiety/depression (p<0.001). Conclusion: This study findings indicate that cataract surgery in people above 50 years not only restore their vision but also brought about a positive improvement in their vision related and general health related quality of life.